Maximal and Explosive Muscle Strength During Hip Adduction Squeeze and Hip Abduction Press Test Using A Handheld Dynamometer: An Intra- and Inter-tester Reliability Study - Lasse Ishøi; Kristian Thorborg; Laura Krohn; Lars Louis Andersen; Asger Møller Nielsen; MIkkel Bek Clausen (North American Sports Medicine Institute, 2023)
# Background Hip adduction and abduction muscle function plays an important role for risk of groin pain in athletes. Maximal isometric strength can be obtained clinically using a handheld dynamometer. However, in very strong athletes this is challenging, as external fixation of the dynamometer is needed for reliable measures. An alternative to unilateral testing, is the long-lever hip adduction squeeze test and a novel bilateral hip abduction press test. While promising intra-tester reliability has been found for maximal strength during the long-lever hip adduction squeeze test, inter-tester reliability may be more challenging during both maximal and explosive strength measurements. # Hypothesis/purpose The aim of the present study was to assess intra- and inter-tester reliability of maximal, and explosive strength during the long lever hip adduction squeeze test and the long lever hip abduction press test in healthy adults using a hand-held dynamometer. # Study design Intra- and interrater reliability study. # Methods Forty-nine healthy subjects were included for intra- (n=20) and inter-tester reliability (n=29). Subjects performed the hip adduction long lever squeeze test and the bilateral hip abduction press test in a randomized order. Maximal isometric strength and early (0-100 ms) and late (0-200 ms) phase rate of force development (explosive muscle strength) was obtained using a hand-held dynamometer. Relative reliability for all tests was assessed using ICC~2,1~ two-way mixed model with absolute agreement, thereby taking bias between testers into account. # Results Maximal isometric strength showed good intra- and inter-tester reliability for adduction (ICC: 0.93-0.97) and abduction (ICC: 0.88-0.92). For 0-200 ms rate of force development, both the squeeze and press test showed good intra-tester reliability (ICC: 0.85-0.87), whereas inter-tester reliability was good for hip adduction squeeze (ICC: 0.75) and moderate for hip abduction press (ICC: 0.71). For 0-100 ms rate of force development, the hip abduction press test showed good intra-tester reliability (ICC: 0.78). Remaining tests for intra- and inter-tester reliability showed moderate reliability (ICC: 0.50-0.71). # Conclusion Assessment of maximal isometric strength in hip adduction squeeze and abduction press test showed good intra- and inter-tester reliability, whereas only 0-200 ms rate of force development demonstrated good intra-tester reliability of both tests. Therefore, rate of force development should preferably be conducted by the same tester, while the long lever squeeze and press test can reliably be used within- and between testers to measure maximal isometric strength. # Level of Evidence 3